A compact disc loaded curved elliptical shaped ultra-wideband MIMO antenna - Satyanarayana, EVV; Kumar, Vivek; Mallikarjun Reddy, D; Siva Paravathi, T; Chandrasekhar Rao, J (International Journal of Engineering and Technology, 2018)
The ultra wide band (UWB) Multiple-Input- Multiple-Output (MIMO) antenna with coplanar waveguide (CPW) having size of 18 x 23 x 0.8mm3 is designed for ultra-wideband (UWB) applications. The designed MIMO antenna contains two symmetrical circular disc loaded curved elliptical monopoles on top of the substrate and common ground plane with Y slot and extended T-shaped stub on bottom of substrate. The T- shape stub is placed on the ground plane to have the better antenna impedance matching and to enhance the isolation between the two antenna ports. To further improve the isolation in between the ports 1 and 2, and also on the ground plane a Y-shaped slot is fixed. Good impedance matching (|S11| < -10dB) in the range from 2.8GHz to 12 GHz is provided by the proposed antenna, and an enhanced isolation of -27dB, low ECC of below 0.002, an acceptable gain of about 7 dBi and an efficiency of above 90%. The obtained result proves that the designed antenna is more appropriate for the portable devices.Â Â